Effect of Intraoperative High Positive End-Expiratory Pressure (PEEP) With Recruitment Maneuvers vs Low PEEP on Postoperative Pulmonary Complications in Obese Patients: A Randomized Clinical Trial - Bluth, Thomas; Serpa Neto, Ary; Schultz, Marcus J; Pelosi, Paolo; Gama de Abreu, Marcelo; Bluth, T; Bobek, I; Canet, J C; Cinnella, G; de Baerdemaeker, L; Gama de Abreu, M; Gregoretti, C; et al. (American Medical Association, 2019)
An intraoperative higher level of positive end-expiratory positive pressure (PEEP) with alveolar recruitment maneuvers improves respiratory function in obese patients undergoing surgery, but the effect on clinical outcomes is uncertain.